Equalization of basic public services enabled by digitization: A study of mechanism and heterogeneity. - Huayi Huang; Zhibing Zhang (PLoS ONE)
Digitalization has penetrated into every aspect of life. However, research on the mechanisms through which digitalization affects the equalization of basic public services, as well as the heterogeneity of its impact on different fields of these services, is still insufficient. Based on the panel data of 30 provincial-level administrative regions in China from 2013 to 2023, this paper studies the mechanism and heterogeneity of the impact of digital development on the equalization of basic public services. The research finds that the improvement of the digital development level can significantly promote the equalization process of basic public services, and this finding remains robust after a series of endogeneity and robustness tests. The discussions on regional heterogeneity and spatial complexity show that digitalization makes a greater contribution to the equalization of basic public services in the central and western regions and the northeast than in the east. However, achieving equalization of basic public services across regions through digitalization is challenging. The development of digitalization and the equalization of basic public services are limited by territorial cohesion in geographical space. Underdeveloped regions have poor access to digitalization for achieving equalization of basic public services. This leads to a 'digital divide' between developed and underdeveloped regions. It also results in a 'low-lying area' phenomenon in basic public services. Additionally, the promoting effect of digitalization on the equalization of different areas of basic public services varies significantly. The effect is strongest for basic living services. It is moderate for environmental protection services and education services. The effect on medical services is not significant.